Towards establishment of a mouse model of circadian abnormality in Alzheimer's disease - Oyegbami, Olaide (2014)
As well as cognitive decline and neuropathological changes, Alzheimer’s disease (AD) is also characterized by non-cognitive behavioural symptoms like restlessness, wandering, agitation, confusion and profound disruptions of circadian rhythms. This group of symptoms is commonly referred to as ‘Sundowning’ and typically occurs in the late afternoon, evening or at night and causes significant problems for Carers. There are no specific drug treatments for these symptoms. One contributory factor is that little is known about the biological basis of these symptoms in Alzheimer’s disease. There is evidence, however, that they may arise as a consequence of abnormal circadian rhythms. Circadian rhythms characterize a number of human physiological and behavioural systems including energy metabolism, sleep-wake cycles, cardiovascular activity, body temperature and locomotor activity. Several studies have demonstrated a role for chromatin modifications in normal circadian function. In mammals, circadian rhythms are generated by a transcriptional-translational feedback loop in which the components of the positive limb (CLOCK and BMAL1), activate the components of the negative limb (the cryptochrome and period proteins). CLOCK possesses intrinsic histone acetyltransferase activity which has been implicated in the circadian control of gene expression. Disrupted rhythmic expression of the core clock genes has also been demonstrated in patients and AD mouse models. With a view to establishing a potential animal model to study the biological basis of Sundowning symptoms, we investigated whether a transgenic mouse model of AD, APPswe/PS1dE9 exhibits circadian alterations in locomotor activity, chromatin modifications and expression of clock genes. The effect of age on altering rhythms in locomotor activity was also investigated. Results show that the APPswe/PS1dE9 mutation alters levels and patterns in locomotor activity at all ages tested, most notably in the activity travelled in the last 2 hours of the dark phase, which is potentially relevant to the disturbance previously reported in AD patients. C57BL/6J and CD1 mice also showed evidence of altered circadian profile with age for locomotor activity. Biomolecular studies revealed altered rhythmic expression of the core clock genes as well as day/night rhythmic chromatin modifications. In summary, these studies reveal altered circadian regulation of locomotor activity, chromatin modification and clock gene expression in APPswe/PS1dE9 mice. They also provide strong evidence that disruption of circadian rhythms of locomotor activity has biomolecular analogies in a widely available model of AD. The APPswe/PS1dE9 model of AD demonstrates the potential to serve as a tool in understanding the neuropathology of circadian abnormalities in Alzheimer’s disease and a model system to test novel therapeutic agents.